Trained Modulation of Sensorimotor Rhythms Can Affect Reaction Time - Boulay, CB (2011)
OBJECTIVE: Brain-computer interface (BCI) technology might be useful for rehabilitation of motor function. This speculation is based on the premise that modifying the EEG will modify behavior, a proposition for which there is limited empirical data. The present study examined the possibility that voluntary modulation of sensorimotor rhythm (SMR) can affect motor behavior in normal human subjects. METHODS: Six individuals performed a cued-reaction task with variable warning periods. A typical variable foreperiod effect was associated with SMR desynchronization. SMR features that correlated with reaction times were then used to control a two-target cursor movement BCI task. Following successful BCI training, the reaction time task was embedded within the cursor movement task. RESULTS: Voluntarily increasing SMR beta rhythms was associated with longer reaction times and decreasing SMR beta rhythms with shorter reaction times. CONCLUSIONS: Voluntary modulation of EEG SMR can affect motor behavior. SIGNIFICANCE: These results encourage studies that integrate BCI training into rehabilitation protocols and examine its capacity to augment restoration of useful motor function.